Copper determination in ethanol fuel samples by anodic stripping voltammetry at a gold microelectrode - Takeuchi, Regina M. [UNESP]; Santos, Andre L. [UNESP]; Medeiros, Maria J.; Stradiotto, Nelson Ramos [UNESP] (Springer Wien, 2009)
A linear sweep anodic stripping voltammetric method was developed for copper determination in commercial ethanol fuel samples by using a gold microelectrode. Under the optimized conditions, a linear range from 0.05 to 1.0 mu M was obtained, with detection limit of 22 nM. The method was employed to determine copper ions in six commercial ethanol fuel samples and the results were compared with those obtained by FAAS. This study showed that for most samples both methods produced concordant results. However, for two samples, copper is distributed in its labile and complexed forms leading to copper contents contrasting with those obtained by flame atomic absorption spectroscopy (FAAS). It was observed that acidification of the samples is a very efficient way to recover copper from its complexed forms. After acidification, the copper contents obtained were concordant with those obtained by FAAS. Thus, the method can be employed to the reliable copper determination in commercial ethanol fuel samples. Moreover, this is the first work providing some insights about copper speciation in commercial ethanol fuel samples.
Keywords: Ethanol fuel samples; Anodic stripping voltammetry; Copper; Gold microelectrode